1999
DOI: 10.1097/00005392-199909010-00035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neoadjuvant Hormonal Therapy on Prostatic Intraepithelial Neoplasia and Its Prognostic Significance

Abstract: While patients treated with neoadjuvant hormonal therapy had significantly lower incidence of prostatic intraepithelial neoplasia, neither prostatic intraepithelial neoplasia nor neoadjuvant hormonal therapy significantly affected PSA recurrence at a median followup of 32 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Prostatic intraepithelial neoplasia was not predictive of PSA (biochemical) failure at 32 months in patients undergoing radical prostatectomy and androgen deprivation therapy [45].…”
Section: Does Prostatic Intraepithelial Neoplasia Predict Cancer Recumentioning
confidence: 90%
See 1 more Smart Citation
“…Prostatic intraepithelial neoplasia was not predictive of PSA (biochemical) failure at 32 months in patients undergoing radical prostatectomy and androgen deprivation therapy [45].…”
Section: Does Prostatic Intraepithelial Neoplasia Predict Cancer Recumentioning
confidence: 90%
“…There is a marked decrease in the prevalence and extent of high-grade PIN in cases after androgen deprivation therapy when compared with untreated cases [45,46]. This decrease is accompanied by epithelial hyperplasia, cytoplasmic clearing, and prominent glandular atrophy, with decreased ratio of glands to stroma.…”
Section: Can Androgen Deprivation Therapy Eliminate Prostatic Intraepmentioning
confidence: 97%
“…However, as we mentioned before, Qian et al [22] showed that HGPIN was more extensive in small cancers than in larger cancers. In their prospective trial, Balaji et al [26] reported that the presence of HGPIN on an RP specimen was not predictive of biological relapse based on a subanalysis of 275 patients. In a more recent publication, Al-Hussain and Epstein [27] suggested that patients previously diagnosed with HGPIN on needle biopsies and treated by RP for prostate cancer would have better outcomes than if they had cancer diagnosed de novo.…”
Section: Discussionmentioning
confidence: 99%
“…The development and identification of acceptable agents to treat high grade PIN would fill a greatly needed therapeutic void [38]. There is evidence that all modes of androgen deprivation that induce acinar atrophy and apoptosis cause regression of high grade PIN [39][40][41][42]. Neoadjuvant hormone deprivation with monthly leuprolide and flutamide, 250 mg orally twice a day for 3 months, resulted in a 50% reduction in high grade PIN [40].…”
Section: Prostatic Intraepithelial Neoplasia Is a Diseasementioning
confidence: 99%
“…There is evidence that all modes of androgen deprivation that induce acinar atrophy and apoptosis cause regression of high grade PIN [39][40][41][42]. Neoadjuvant hormone deprivation with monthly leuprolide and flutamide, 250 mg orally twice a day for 3 months, resulted in a 50% reduction in high grade PIN [40]. Longer therapy with 6 months of neoadjuvant androgen deprivation therapy prior to radical prostatectomy in the European Randomized Study of Screening for Prostate Cancer (ERSPC) study reduced high grade PIN even more [43].…”
Section: Prostatic Intraepithelial Neoplasia Is a Diseasementioning
confidence: 99%